Analisis Pembentukan Karakter Kemandirian Anak Asuh Dalam Meningkatkan Kemandirian Anak di Panti Asuhan Darul Aitam Kecamatan Medan Area Kota Medan - Alfan Aria Tama (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2023)
Seeing the many sad conditions of children whose lives are not like other children in general, namely that there are still abandoned children, the result of divorce, orphans, orphans who no longer have parents, as well as children whose knowledge needs are not fulfilled due to their families not having sufficient economy. Those who are deprived of basic rights as children such as: education, protection, care and love from parents, even though loving and being loved is the nature of every child. One way that can be done so that children remain in good care is to accommodate these children in an orphanage, as an institution in coaching, character building which replaces the function and role of the family. In the orphanage abandoned children who are cared for by the orphanage do not only get education but also get protection and good service and the facilities provided by the orphanage such as delivery services, formal and non-formal education services, health services, food and clothing. Orphanages also pay attention by giving affection and useful advice. In addition to receiving formal education, the orphans also receive education in terms of morals, ethics, morals, and good manners. Everything is taught to foster children by the caretakers of the orphanage by guiding and advising them to form independent and good personalities in society. This is interesting to study. This research was conducted at the Darul Aitam Orphanage in Medan City using qualitative research using data collection techniques, namely literature studies, observations and interviews and the data obtained in the field was described, so that conclusions could be drawn from the research results. The main informants are the foster children in the orphanage. There are 4 character building programs for foster children, namely emotional, intellectual, social and economic. And based on the results of the research the researcher suggests that the program be more structured and more detailed so that there are no programs that are not executed